Asuhan Keperawatan dengan Teknik Latihan Genggam Bola untuk Meningkatkan Kekuatan Otot Ekstremitas Atas - Faramita Hangkiho; Mega Lumingkewas (JURNAL ILMIAH KESEHATAN MANADO, 2026)
Non-hemorrhagic stroke is a major cause of impaired physical mobility due to muscle weakness and decreased motor function. This condition makes it difficult for patients to perform daily activities and impacts quality of life. This study used a case study design (descriptive) on a 50-year-old male patient with a medical diagnosis of non-hemorrhagic stroke. The intervention provided was ball grip exercises two to three times daily for three days with a duration of 10–15 minutes per session. Data collection was carried out through direct observation of muscle strength, as well as daily subjective and objective patient evaluations. The results showed an increase in upper extremity muscle strength from a scale of 2/5 on the first day to 4/5 on the third day. The patient also showed increased tolerance for ambulation activities and the ability to grip objects stably. Ball grip exercises have been shown to help stimulate neuromuscular function, improve blood circulation, and accelerate motor recovery in stroke patients. Conclusion: Regular implementation of ball grip exercises is effective in increasing upper extremity muscle strength in non-hemorrhagic stroke patients with impaired physical mobility. This intervention can be used as one of the EBN-based non-pharmacological therapies in the nursing rehabilitation program for stroke patients.